Impact of Covid-19 Lockdown on Agricultural Production - Meena, Akshay; Meena, Anita (Universitas Prasetiya Mulya, 2022)
This study aims to assess the impact of the Covid-19 lockdown on the agricultural crop production in India and identify the factors affecting the agricultural crop production in India during the lockdown period. Due to the pandemic, production of Rabi crops such as Jowar and coarse cereals have declined, and the growth rate of Kharif crops such as Bajra and coarse cereals production have also been dropped. Among the horticulture crops, the growth rate of fruit production has been adversely affected by the restrictions imposed during the lockdown. The fertilizer consumption, annual rainfall, pesticides consumption and storage capacity are identified as major determinants affecting the agricultural crop production in the country during the lockdown period.